DIAGNOSIS AND MANAGEMENT POST TRAUMATIC STRESS DISORDER IN SEXUAL ABUSE - Apriliani Saniti, Ni Made (E-Jurnal Medika Udayana; vol 2 no6(2013):e-jurnal medika udayana, 2013)
Traumatic experiences may happen anytime in our life. The more terrible the situation, the bigger chance for a person to have post traumatic psychological problem, that is the Post Traumatic Stress Disorder (PTSD). Sexual abuse is a kind of traumatic event that caused psychological trauma/stress for the victim. In order to be able to manage patient with PTSD, physician should comprehend properties regarding PTSD, including proper treatment and management. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: stress, post traumatic event, sexual abuse